Effect of different structures of carbon supports for cathode catalyst on performance of direct methanol fuel cell. (21st January 2016) - Liu, Jing; Liu, Chun-Tao; Zhao, Lei; Zhang, Jing-Jia; Zhang, Li-Mei; Wang, Zhen-Bo
Abstract: Carbon black (CB), multiwalled carbon nanotubes (MWNTs), reduced graphene oxide (rGO) are used as the cathode catalyst supports to investigate the effect on direct methanol fuel cell (DMFC) performance by using rotating disk electrode and fuel cell testing. The results of linear sweep voltammetry (LSV) and cyclic voltammetry (CV) show that the electrocatalytic activity sequence for oxygen reduction reaction (ORR) is Pt/rGO > Pt/MWNTs > Pt/C catalysts. The single cell tests results show that the maximum power densities of DMFC with Pt/C, Pt/MWNTs and Pt/rGO cathode catalysts are 74.0, 74.2 and 3.3 mW cm −2, respectively. The experimental results indicate that the performance of DMFC is substantially influenced by the structures of cathode catalyst supports. The significant differences in DMFCs performance are due to the compression ratios and hydrophilic/hydrophobic properties of catalyst layers with different structures of carbon supports, which strongly affect electrochemical active sites and mass transport in cathode catalyst layers. Long-term testing of DMFCs indicates that Pt/MWNTs exhibits superior stability. Considering the factors of the power and lifetime comprehensively, MWNTs is optimal candidate among the three investigated carbon supports. Graphical abstract: The significant differences in DMFCs performance are due to the compression ratios and hydrophilic/hydrophobic properties of catalyst layers with different structures of carbon supports, which affect electrochemical active sites and mass transport in cathode catalyst layers. Highlights: Effect of different structures of cathode carbon supports on DMFC performance is studied. Compression ratio of catalyst layer is critical for MEA on DMFC. 2D structured rGO sheets exhibit a strong tendency to horizontal stacking, during the MEA fabrication. MWNTs is optimal for cathode catalyst support in DMFC among CB, MWNTs and rGO.